Process of socio - economic development - "Dubey, K N" (Jaipur, 1992)
The book is an in depth geographical analysis of the development process in Uttar Pradesh based on empirical research. It sets its priority for conceptual clarity and methodological rigour on any point of discussion. An attempt has been made not only to discuss the spatial patterns of all that is relevant to development but also to spell out planning strategies which are region specific. The book will be useful not only to geographers but also to other social scientists, planners and administrators.
Keywords: Economics